The Position of The Village Head as Mediator in Resolving Disputes in the Village in Terara District, East Lombok Regency - Azro’I, Achmad; Asmara, Galang; Minollah, (International Journal of Scientific Research and Management (IJSRM), 2022)
The purpose of the study was to analyze the position and legality of the village head in resolving disputes through mediation and to analyze the legal implications of the peace agreement produced by the village head as a mediator in resolving disputes in the village. The type of research used is empirical juridical, with legal materials in the form of laws governing villages, village heads, certified mediators and other complements. The sample villages were Sukadana, Jengik, Pandanduri, Santong, Terara and Suradadi. The findings in this study indicate that the village head has a clear position as a mediator, because it is the duty, authority and obligation of the village head in resolving disputes of his citizens. Village heads who do not position themselves as mediators, if there are residents who are in dispute can be subject to administrative sanctions (oral, written, temporary dismissal and dismissal; article 26 paragraph 4 and article 28 of Law No. 6 of 2014). In the context of legality, the existence of work guarantees on the law gives an indication that the resulting peace products have legal force, but the facts in PerMA No. 1 of 2016 is only given the title as a peace agreement and a lawsuit needs to be made to the court to become a peace deed. Facts on the ground, especially in some sample villages in East Lombok Regency as the parties to the dispute, where the village head has obtained peace, including between village heads, is obeyed by all parties. In order to maintain certainty, important suggestions in this study for disputes that have a large nominal value or large impact should be submitted to the court to become a peace deed. The government through its various agencies should provide training to all village heads to become certified mediators.